Penyerapan Tenaga Kerja pada Sentra Industri Rajutan Binong Jati Kota Bandung - Fina Marliana Darusman; Endang Rostiana (Faculty of Economics and Business, University of Pasundan, 2015)
In order to develop industrial sector, Kota Bandung develop ten industrial and trades areas. One of the industrial and trades area is Binong Jati Knitting Industrial and Trade Centre, which is potentially in absorbing the employment. The objectives of the study are to identify the condition of Binong Jati Knitting Industrial and Trade Centre today and to analyze relationship between labor absorption and several economic variables in Binong Jati Knitting Industrial and Trade Centre. This research use primary data which collected from 55 business unit as a sample from 120 population. Analysis method is descriptive statistic and linier regression. According to our field observation and interview, most of the unit business in Binong Jati Knitting Industrial and Trade Centre is small and middle scale industries. In term of number of employment, Binong Jati Knitting Industrial and Trade Centre is in the second rank after Cibaduyut Shoes Industrial Centre. In recent years, units business and number of workers has decreased. According to regression analysis, in Binong Jati Knitting Industrial and Trade Centre, size of employment is negativelly related with wage rate, positively related with price of raw material, number of sales, labor productivity, and number of machine units.